Factors influencing students volunteer satisfaction in volunteering activities in rural area of Sabah. - Mohamad Amirul Zulmajdi; Nur Sajida Peduka; Nur Shakirah Ab Rahim; Nurul Nadia Juharei (2021)
This study focuses on understanding Factors Influencing Student Volunteer Satisfaction in Volunteering Activities at Rural Area of Sabah. This study examines the relationship between personal values that influenced volunteer satisfaction among students in volunteering activities at rural area in Sabah, the relationship between factors of behavioural intention that influenced volunteer satisfaction among students in volunteering activities at the rural area, Sabah, and aims to analyse the relationship between factors of social needs that influenced volunteer satisfaction among students in volunteering activities at the rural area, Sabah. In order to obtain the results of this study, quantitative methodologies were employed to organise data gathering and analysis. Purposive sampling was used and answers from 384 respondents of public and private institutions students were collected. All of the data was analysed using descriptive analysis, reliability testing, and Pearson correlation. The result supports all variables. In the results of this result found that the average university student understands about the motivational factors that influence satisfaction towards voluntary activities. This research and data can be used as reference material for industry stakeholders to ensure that students from public and private institutions are more motivated in volunteering.